Apoptosis: why and how does it occur in biology? - YILMAZ, YUSUF (WILEY, 2011)
The literature on apoptosis has grown tremendously in recent years, and the mechanisms that are involved in this programmed cell death pathway have been enlightened. It is now known that apoptosis takes place starting from early development to adult stage for the homeostasis of multicellular organisms, during disease development and in response to different stimuli in many different systems. In this review, we attempted to summarize the current knowledge on the circumstances and the mechanisms that lead to induction of apoptosis, while going over the molecular details of the modulator and mediators of apoptosis as well as drawing the lines between programmed and non-programmed cell death pathways. The review will particularly focus on Bcl-2 family proteins, the role of different caspases in the process of apoptosis, and their inhibitors as well as the importance of apoptosis during different disease states. Understanding the molecular mechanisms involved in apoptosis better will make a big impact on human diseases, particularly cancer, and its management in the clinics. Copyright (C) 2011 John Wiley & Sons, Ltd.
Keywords: programmed cell death; apoptosis; necrosis; apoptosis-inducing factors (AIFs); caspase; inhibitor of apoptosis proteins (IAPs); Bcl-2 family; X-LINKED INHIBITOR; APO-1/FAS RECEPTOR/LIGAND SYSTEM; CASPASE-CLEAVED CYTOKERATIN-18; BCL-2 FAMILY PROTEINS; CELLS IN-VITRO; FAS-LIGAND; CYTOCHROME-C; MITOCHONDRIAL APOPTOSIS; CHROMOSOME-SEGREGATION; BH3-ONLY PROTEINS